Regulation of the SREBP transcription factors by mTORC1. (22nd March 2011) - Lewis, Caroline A.; Griffiths, Beatrice; Santos, Claudio R.; Pende, Mario; Schulze, Almut
Abstract : In recent years several reports have linked mTORC1 (mammalian target of rapamycin complex 1) to lipogenesis via the SREBPs (sterol-regulatory-element-binding proteins). SREBPs regulate the expression of genes encoding enzymes required for fatty acid and cholesterol biosynthesis. Lipid metabolism is perturbed in some diseases and SREBP target genes, such as FASN (fatty acid synthase), have been shown to be up-regulated in some cancers. We have previously shown that mTORC1 plays a role in SREBP activation and Akt/PKB (protein kinase B)-dependent de novo lipogenesis. Our findings suggest that mTORC1 plays a crucial role in the activation of SREBP and that the activation of lipid biosynthesis through the induction of SREBP could be part of a regulatory pathway that co-ordinates protein and lipid biosynthesis during cell growth. In the present paper, we discuss the increasing amount of data supporting the potential mechanisms of mTORC1-dependent activation of SREBP as well as the implications of this signalling pathway in cancer.